THE ANTIOXIDANT ACETYLCYSTEINE REDUCES OXIDATIVE STRESS BY DECREASING LEVEL OF AOPPS - Lazarova, Marie; Stejskal, David; Lacnak, Borek; Vaclavik, Jan; Adamovska, Sylva; Ochmanova, Radka; Hanak, Vaclav; Skacelova, Martina (Biomedical papers, 2004)
Oxidative stress and especially its connection with many diseases has been discussed much recently. Among markers of oxidative stress there appear new and quite specific ones called advanced oxidation protein products (AOPPs). We tried to influence the level of AOPPs by an antioxidant therapy with N-acetylcysteine. Fourteen individuals with many cardiovascular risk factors were examined. All these patients were administered acetylcysteine (NAC) 600 mg/day orally during 20 days. Before starting the therapy we determined AOPP, albumin cobalt binding (ACB), glucose, creatinine, urea, ALT, AST, cholesterol, LDL, HDL and triglycerides values in peripheral venous blood in all individuals. After finishing our intervention we determined AOPP, ACB and glucose level again. Our results show a statistically significant decrease in AOPP levels after 20-day N-acetylcysteine therapy (medians, initially 82.2, at study end 74.3 umol/l, p = 0.039). We demonstrate a significant decrease in AOPP levels after 20-day N-acetylcysteine therapy in dose 600 mg/day.
Keywords: Antioxidant therapy/N-acetylcysteine/NAC/AOPP/ACB